Methodical and multimedia environment for the acqusition of ICT competemces in the field of logo programming of future compulsory education teachers - Rogulja, Nataša (Array, 2014)
The purpose of this paper was to propose and explore the methodical and multimedia environment required for the acquisition of ICT competences in the field of Logo programming of future compulsory education teachers. According to the student teachers' education curriculum, among other ICT competence requirements, the future teachers are to acquire relevant knowledge and skills in Logo programming. In order to determine the level of competence acquired, a methodical-qualitative evaluation of the environment, in the form of a web application, has been conducted by 50 students of The Faculty of Teacher Education of the University of Zagreb. Research results show that the environment contributes to the more effective acquisition of ICT competences of future teachers, especially in the field of computer programming.